2016
DOI: 10.1167/iovs.16-19686
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Aqueous Flare and Epiretinal Membrane in Retinitis Pigmentosa

Abstract: PURPOSE. Epiretinal membrane (ERM) is a frequent macular complication in patients with retinitis pigmentosa (RP). The etiology of ERM formation in RP is largely unknown. The purpose of this study was to investigate the association between aqueous flare, a surrogate index of intraocular inflammation, and ERM secondary to RP. METHODS.We retrospectively studied a total of 206 eyes of 117 patients who were diagnosed with typical RP. Aqueous flare values were measured consecutively in 2012 and 2013 using a laser fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…The aqueous flare was measured with a Kowa FM-600 laser flare meter (Kowa, Nagoya, Japan) as described in our previous studies. 12,13 Flare values were obtained 30 minutes after pupillary dilation with 0.5% tropicamide and 5% phenylephrine hydrochloride. Five measurements were taken and averaged in each eye.…”
Section: Laser Flare Photometrymentioning
confidence: 99%
“…The aqueous flare was measured with a Kowa FM-600 laser flare meter (Kowa, Nagoya, Japan) as described in our previous studies. 12,13 Flare values were obtained 30 minutes after pupillary dilation with 0.5% tropicamide and 5% phenylephrine hydrochloride. Five measurements were taken and averaged in each eye.…”
Section: Laser Flare Photometrymentioning
confidence: 99%
“…Visual acuity can also be affected by the development of various types of macular complications, such as epiretinal membrane, cystoid macular oedema, macular hole, vitreomacular traction and macular degeneration, which generate further variation in central visual function 9 10. Many of these macular complications are also observed in other intraocular inflammatory diseases, such as uveitis,11 and the modest inflammation that accompanies RP12 may also contribute to macular pathology 13…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of ERM formation remains unclear. However, it may include (1) idiopathic preretinal glial cell proliferation, (2) in ammation revealed by elevated aqueous are, and (3) chronic macular-vitreous traction [15][16][17]. Our results demonstrated that CME was the second most common macular abnormality, and this coincided with results from an Italian population for which Testa et al investigated macular abnormalities in 581 RP subjects [1] and found that the most frequent abnormalities was CME (20.4% eyes), followed by ERM (15.6%), VMT (5%), and MH (2%).…”
Section: Discussionmentioning
confidence: 99%